Impact Analysis of Dynamics Performance of Center-locomotive of Daqin Railway 21 000 t Train in Different Locomotive Combinations - YANG Xiangjian; GUO Zhijie; MIAO Shudong; XIE Xing (机车电传动)
By comparing the dynamics performance of the center-locomotive in different locomotive combinations (HXD2+HXD1 or HXD1+HXD1) at the speed-regulation braking condition of Daqin railway 21 000 t heavy haul train, the conclusion was obtained that the center-locomotive dynamics performance of HXD2+HXD1 combination was better than HXD2+HXD1 combination, and the signal delay had big impact on center-locomotive impulse.